Denial of service attack in wireless data network: A survey - Singh, Rahul Sourav; Prasad, Ajay; Moven, Roselina Maria; Deva Sarma, Hiren Kumar (2017 Devices for Integrated Circuit (DevIC), 2017)
Wireless networks is one of the dominant technology trends in this digital era. Due to the broadcast nature of wireless network, wireless air interface is open and accessible to all types of users, which turned to be a numerous unique challenges on their security to researchers. While the set of challenges in wireless networks are diverse, we focus on Denial of service attack in Wireless Network in this paper. Denial of Service (DoS) attack targets to degrade the efficient use of network resources and disrupts the essential services in the network. DoS attack could be considered as one of the major threats against Wireless Network security. First, we propose effects of DoS attack on Wireless Network. Further, various DoS attacks on different layers of TCP are proposed.